2014
DOI: 10.3389/fnins.2014.00359
|View full text |Cite
|
Sign up to set email alerts
|

Barrier mechanisms in neonatal stroke

Abstract: Clinical data continue to reveal that the incidence of perinatal stroke is high, similar to that in the elderly. Perinatal stroke leads to significant morbidity and severe long-term neurological and cognitive deficits, including cerebral palsy. Experimental models of cerebral ischemia in neonatal rodents have shown that the pathophysiology of perinatal brain damage is multifactorial. Cerebral vasculature undergoes substantial structural and functional changes during early postnatal brain development. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 106 publications
(125 reference statements)
0
31
0
2
Order By: Relevance
“…The challenge in the field of neonatal brain injury has been the difficulty to clinically discern the mild-moderate NE severity within the short therapeutic window after birth. A sensitive and specific physiological marker that directly assesses neurovascular function in real-time, and is a marker of clinical outcomes, is critically needed to guide therapies8910.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge in the field of neonatal brain injury has been the difficulty to clinically discern the mild-moderate NE severity within the short therapeutic window after birth. A sensitive and specific physiological marker that directly assesses neurovascular function in real-time, and is a marker of clinical outcomes, is critically needed to guide therapies8910.…”
mentioning
confidence: 99%
“…The neurovascular unit consists of neurons, astrocytes, endothelial cells of blood–brain barrier (BBB), myocytes, pericytes and extracellular matrix components which play an important role in the delivery of oxygen and nutrients to the brain and the maintenance of cerebral circulation homeostasis91112. Individual metrics of electroencephalography6131415 and near-infrared spectroscopy (NIRS)1617 have been used independently to assess the function of neurovascular unit, but the ability to study coupling in real time of NIRS and EEG in HIE has received little attention11171819 These methods demonstrated that a severe asphyxia insult leads to impaired function, but the extent of dysfunctional neurovascular coupling (NVC), and its impact on clinical outcome of newborns with encephalopathy cannot be currently assessed in real time due to limited methodology2021.…”
mentioning
confidence: 99%
“…Recovery mechanisms are complex, but unlike in older children or adults, the brain of the newborn is a very dynamic system, with an important part of synaptogenesis [15]. Some authors [16,17] have reported the important role of cell proliferation and migration of the sub-ventricular zone. Some of these cells are multipotent and provide training for neuroblasts and glial cells [16].…”
Section: Commentsmentioning
confidence: 99%
“…The ECM of the basement membrane continuously undergoes controlled remodeling during development and is important in hypoxic-ischemic brain injury and pediatric stroke [8][9][10][11][12][13]. Remodeling of the ECM is facilitated primarily by matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%